Pre-Manichaean Beliefs of the Uyghurs II: Other Religious Elements - Erkoç, Hayrettin İhsan (Journal of religious history, 2023)
The original beliefs of the Uyghurs, which have been overshadowed by their conversion to Manichaeism and Buddhism, have not been thoroughly studied until recently. However, Uyghur inscriptions as well as Chinese and Islamic sources provide us with some information regarding their beliefs. In the first part of this article series, the Uyghurs' belief in various cults related to celestial and natural beings was explored. In this second part, other religious elements will be analysed. The Uyghurs possessed a cult of ancestors, in which souls were believed to fly away. Funeral ceremonies called yoγ are noted to contain animal and human sacrifices as well as self-harming activities. Worship included animal sacrifice and idol worship. Qam (shamans) performed rituals, including fortune telling and weather magic. Religious terminology included qut (divine fortune), ülüg (destiny), yol (luck), and yazuq (sin). They held the numbers seven and nine in high esteem as sacred numbers, while sacred lights descending from the sky and the sacred consort of a mythological ruler were important motifs. Although some scholars have written that Buddhism was practiced by the Uyghurs before their conversion to Manichaeism in the 760s, further research has shown that this was not the case. This article also reveals how their ancient beliefs survived even after their conversions to major religions.